El Estallido Social and ICS Chile 2019 - Marivic Wyndham (PORTAL: Journal of Multidisciplinary International Studies)
This reflection recounts the extraordinary experiences of the 2019 In-Country Study (ICS) Chile cohort during Chile’s Estallido Social, a period of intense social and political unrest. Despite facing immense challenges, including civil unrest and disruptions to their studies, the students demonstrated resilience, adaptability, and a deep commitment to their host communities. Through their collective efforts and independent explorations of Chilean society, they exemplified the global citizenship and intercultural skills nurtured in the International Studies program.